Electronic materials science - Irene, Eugene A. (John Wiley, 2005)
A thorough introduction to fundamental principles and applicationsFrom its beginnings in metallurgy and ceramics, materials science now encompasses such high- tech fields as microelectronics, polymers, biomaterials, and nanotechnology. Electronic Materials Science presents the fundamentals of the subject in a detailed fashion for a multidisciplinary audience.